Nitric Oxide Synthase - Simple Enzyme-Complex Roles 2017
DOI: 10.5772/67025
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endothelial Nitric Oxide Synthase in Glucocorticoid- Induced Hypertension: An Overview of Experimental Data

Abstract: Imbalances in the synthesis or in the bioavailability of nitric oxide (NO), the freely diffusible vasodilator, in myocardial endothelial cells were demonstrated to be crucial in the development of hypertension. Glucocorticoids (GCs) are widely used as immunomodulators. One of the numerous side effects of GC therapy is hypertension arising from reduced release of the endothelium-derived NO. GCs can modulate NO synthesis by targeting the genes involved in it, like nitric oxide synthase (NOS) and guanosine tripho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…however, when compared to the research that has been carried out by Ugusman et al, 2020 which used a dose of dexamethasone 0.02 mg/kg BW without the administration of a 5% NaCl solution instead of drinking water and caused hypertension after 28 days of administration, the addition of salt solution in this study did not accelerate the occurrence of hypertension. On the other hand, dexamethasone causes a decrease in nitric oxide (NO) levels only through a downregulation of eNOS mRNA (Blecharz-Lang & Burek, 2017). Purpose of the addition of a 5% NaCl solution in this study is to cause the uncoupling of eNOS so that it actually lowers the level of nitric oxide and causes endothelial dysfunction (Li et al, 2016) as a result of the research that has been done by Satoh et al, 2010(Satoh et al, 2010.…”
Section: Resultsmentioning
confidence: 94%
“…however, when compared to the research that has been carried out by Ugusman et al, 2020 which used a dose of dexamethasone 0.02 mg/kg BW without the administration of a 5% NaCl solution instead of drinking water and caused hypertension after 28 days of administration, the addition of salt solution in this study did not accelerate the occurrence of hypertension. On the other hand, dexamethasone causes a decrease in nitric oxide (NO) levels only through a downregulation of eNOS mRNA (Blecharz-Lang & Burek, 2017). Purpose of the addition of a 5% NaCl solution in this study is to cause the uncoupling of eNOS so that it actually lowers the level of nitric oxide and causes endothelial dysfunction (Li et al, 2016) as a result of the research that has been done by Satoh et al, 2010(Satoh et al, 2010.…”
Section: Resultsmentioning
confidence: 94%
“…The attenuation of the insulin-mediated vasodilation in our study is due to reduction of NO bioavailability, mediated by a decrease in eNOS expression. Studies have demonstrated that GC treatment significantly down-regulates eNOS expression [16,34]. These changes in eNOS expression following GC treatment may have been caused by uncoupling of eNOS, through inhibiting essential cofactors, becoming inactive and reducing NO production [35].…”
Section: Plos Onementioning
confidence: 99%